Seasonal Elevated and Variable Groundwater Iron in Chandrapur District, Central India - Rahul K Kamble (Indonesian Journal of Environmental Management and Sustainability, 2019)
Groundwater iron concentrations were monitored from rural area of the Chandrapur district, Central India during winter, summer and post-monsoon at 36 sampling locations so as to map and quantify its levels. Grab sampling was carried out for groundwater sampling from dug wells (DW) (n=2, 5.55%) and hand pumps (HP) (n=34, 94.44%). Iron concentration was determined by acid digestion method and further analysis by using ICP-OES. Maximum iron concentration in winter was 47.100 mg/L (Ballarpur, HP), 3.825 mg/L (Ballarpur, HP) in summer and 3.714 mg/L (Visapur, HP) in post-monsoon. Average iron concentration in winter, summer, and post-monsoon was 3.522 mg/L, 0.730 mg/L and 0.582 mg/L respectively, which were above the acceptable limit of the Indian Standard (IS) and WHO aesthetic limit for iron (0.3 mg/L). Seasonal variation in groundwater iron concentration was observed in the order of winter>post-monsoon>summer. Distribution of iron with IS revealed a number of samples above the permissible limit and in the order of summer>winter>post-monsoon. In case of a distribution on WHO, JECFA and IOM recommendations, number of samples in high to very high category was in the order of winter>summer>post-monsoon. It can be concluded that seasonal elevated and variable groundwater iron concentration was observed from the study area. A number of samples had the concentration several times above the IS acceptable limit and WHO aesthetic cut-off. The plausible reasons for these observations can be assigned to geology, water source type (HP/DW), space and time, the proximity of water source to minerals and ores present in the earth crust, physicochemical characteristics of water and dissolution and leaching of metal in groundwater